Misinformation in Experimental Political Science - Barnfield, Matthew (Perspectives on politics, 2023)
The American Political Science Association recently cautioned against the use of misinformation (giving research participants false information about the state of the world) in research with human subjects. This recommendation signals a growing recognition, as experimental research itself grows in prevalence in political science, that deceptive practices pose ethical problems. But what is wrong with misinformation in particular? I argue that while this question certainly has an ethical dimension, misinformation is bad for inference too. Misinformation moves us away from answering questions about the political world effectively. I propose a straightforward, intuitive solution to this twofold problem: tell the truth.